Blockchain - Laurence, Tiana (--For dummies., 2019)
"Blockchain is the techno-magic that enables cryptocurrencies and impacts the worlds of finance, insurance, supply chain management, and others. But you don't need to be a programmer or financial wizard to understand blockchain; you just need this book! It explains blockchain basics, smart contracts, and cryptocurrencies, with real-world examples showing how blockchains functions and where they ad value. Learn how to interact with a blockchain, tour key blockchains, see how they disrupt huge industries, and much more." -- Back cover.